The Mediating Role of Agency Cost between Corporate Governance and Financial Performance: Evidence from Pakistan Stock Exchange - Sadia Bint Raza; Sheikh, Salman Masood; Rahman, Saif Ur (iRASD Journal of Economics, 2024)
The study's main objective is to investigate the relationship between corporate governance and the financial success of companies listed on the Pakistan Stock Exchange 100 index in the presence of an agency cost. However, the second goal of this study is to investigate the mediating effect of corporate governance on the financial performance of enterprises listed on the Pakistan Stock Exchange 100 index. The results confirm that leverage, board size, and CEO have a favorable association with ROE. Board independence, MOWN, and institutional investors show a negative correlation with ROE. Furthermore, CEO duality is a major predictor of corporate performance. Duality has a considerable beneficial effect on ROE. According to the studies, institutional owners prefer to receive profits quickly rather than participate in new breakthroughs, which is not beneficial to the organization's long-term development. A statistically significant negative connection is discovered with ROE, indicating that more managerial ownership affects business performance. Too frequent meeting is not always useful and help to improve the firm’s performance because it involves more managerial time consumption, more increase expenses in term of travel expenses and directors’ fees.